DUKUNGAN FAKTOR-FAKTOR ORGANISASI DAN INDIVIDU DALAM MEMBENTUK KINERJA DOSEN PADA SEKOLAH TINGGI ILMU EKONOMI AMM MATARAM - ZULKARNAEN ZULKARNAEN; NIZAR HAMDI (Universitas Mahasaraswati K. Mataram, 2022)
This study aims to identify organizational factors and individual factors that shape performance and analyze organizational factors and individual factors that have a dominant contribution to the performance of lecturers at STIE AMM Mataram. This type of research is descriptive exploratory research. Data were collected by questionnaire and documentation techniques. Data analysis using factor analysis. Based on factor analysis from the results of factor grouping based on factor loading variance, the 22 existing factors were reduced to 7 groups of factors that had a minimum factor loading value of 0.5, namely: The first group consisted of motivation with a loading factor of 0.902, education with a loading factor of 0.890. policies and rules with a loading factor of 0.852, technology with a loading factor of 0.809, abilities and skills with a loading factor of 0.661 and sanctions with a loading factor of 0.652. The second group consists of experience with a loading factor of 0.949, learning capacity with a loading factor of 0.946, characteristics with a loading factor of 0.727, and ethnicity or race with a loading factor of 0.554. The third group consists of resources with a loading factor of 0.837, leadership with a loading factor of 0.764, and age with a loading factor of 0.607. The fourth group consisted of family background with a loading factor of 0.879, gender with a loading factor of 0.641, and personality with a loading factor of 0.557. The fifth group consists of an organizational structure with a loading factor of 0.718, rewards and rewards with a loading factor of 0.675. The sixth group consisted of attitudes with a loading factor of 0.923 and job design with a loading factor of 0.728. The seventh group consisted of social class with a loading factor of 0.720 and perceptions with a loading factor of 0.588. Based on the loading variance factor grouping above, there are 6 most dominant factors shaping the performance of lecturers at STIE AMM Mataram, namely motivation, education, abilities and skills which are individual factors and policies and rules, technology and sanctions which are organizational factors.